Use of SnOx:F in the Recycling of Silicon Solar Cells - Lima,Francisco Marcone (2017)
Amongst the many parts of a silicon cells photovoltaic module, silicon is the most important and expensive constituent. Thus, research on silicon recycling from damaged cells can lead to economic and environmental benefits. In this work, the broken silicon cells were tailored to function along with the fluorine-doped tin oxide as the transparent electric conductors. The broken silicon cells were analyzed by the current density versus voltage plots, together with the Mott-Schottky, X-rays diffraction and fluorescence analysis. Under light, the damaged cells sandwiched between the two transparent electric conductors presented photovoltaic effect. However, such effect was not obtained after the removal of the antireflection layer due to the destruction of the n-type layer as demonstrated by the Mott-Schottky analysis. The X-rays diffraction revealed samples rich on silicon atoms and the presence of aluminum atoms as impurity.